Marchiafava-Bignami Disease: Longitudinal MR Imaging and MR Spectroscopy Study - Gambini, Anna; Falini, Andrea; Moiola, Lucia; Comi, Giancarlo; Scotti, Giuseppe (American Journal of Neuroradiology, 2003)
Summary: A case of Marchiafava-Bignami disease was serially evaluated with MR imaging and MR spectroscopy at 1, 2, 4, and 11 months after the onset of symptoms. The first MR imaging study showed extensive abnormal signal intensity of the corpus callosum without macroscopic changes; a diagnosis of Marchiafava-Bignami disease was made, and vitamin therapy was initiated. Follow-up studies showed progressive reduction of signal intensity abnormalities and residual callosal atrophy. MR spectroscopy revealed progressive reduction of the N-acetylaspartate:creatine ratio, with partial recovery in the last study, and a normalization of the choline:creatine ratio, which was initially slightly increased. Lactate was detectable during the subacute phase and was replaced by lipids after 4 months. This study confirmed the role of MR imaging in diagnosing Marchiafava-Bignami disease and particularly the value of MR spectroscopy in focusing the pathogenesis of the disease, monitoring its evolution and changes related to therapy.